Finanšu dokumentu aprites aktuālās problēmas e-pārvaldes kontekstā - Grīnerte, Santa (Latvijas Universitāte, 2012)
Maģistra darba mērķis ir aprakstīt un novērtēt finanšu dokumentu apriti un plūsmu e-pārvaldes kontekstā, t.i.,–raksturot e-pārvaldi un tās ieviešanu Latvijā, kā arī noteikt problēmas, kas kavē finanšu dokumentu elektronisku plūsmu e-pārvaldes kontekstā. Pētījuma empīrisko bāzi veido konkrēta mazā uzņēmuma finanšu dokumentu aprites un plūsmas analīze. Pētījuma rezultātā tiek secināts, ka finanšu dokumentu e-aprite tiek ieviesta lēni, jo ir vairāki šķēršļi, kas to kavē–normatīvo aktu, likumdošanas trūkums, neērta e-paraksta lietošana, kā arī vairāki t.s. cilvēciskie faktori.

This master thesis deals with the financial document circulation problem areas of e-government context, and also evaluates the financial document flow of enterprise e-government context. The study aims to assess the financial documents the flow of e-government context. And the great challenges of the study werw identified–to characterize the e-government and fix the problems that impede the flow of financial documents in the context of e-government and to assess the financial documents the flow of the company’s e-government context.Results of this study is useful for all those interested in the situation already existing in the document the movement of the e-form industry professionals, students, ect. In assessing the results of a study it is concluded that e-bills are beings introduced very slowly, because there are some obstacles–lack of regulatory legislation, awkward, and also the human factor.
Actual problems of circulation of financial documents in the context of e-government
Keywords: Bibliotēkzinātne